2015
DOI: 10.1093/ofid/ofv119
|View full text |Cite
|
Sign up to set email alerts
|

Improving Influenza and Pneumococcal Vaccination Rates in Ambulatory Specialty Practices

Abstract: Background. Influenza and pneumococcal vaccinations are recommended for elderly and high-risk patients; however, rates of adherence are low. We sought to implement influenza and pneumococcal vaccine initiatives in 4 different ambulatory specialty practices, using 3 unique approaches.Methods. Four specialties with high-risk patient populations were selected for intervention: allergy (asthma), infectious disease (ID) (human immunodeficiency virus), pulmonary (chronic lung disease), and rheumatology (immunocompro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
16
2
Order By: Relevance
“…In contrast to the present study, Pennant et al documented significantly higher vaccination rates for pneumococci (after intervention: chronic lung disease: 79%, rheumatology disease: 87%), but especially for influenza (after intervention: allergy: 64%, infectious disease: 86%). However, the pre‐intervention vaccination rates were already well above the vaccination rates of our present study . In a study conducted by Sansom et al in a sexually transmitted disease clinic for men who have sexual relations with other men, a telephone reminder was ineffective regarding the proportion of patients who completed the basic immunization with the third dose of the hepatitis B vaccination (control group: 59.2% [n = 145], intervention group: 56.3% [n = 157]) or the second dose of the hepatitis A vaccination (control group: 62.9% [n = 154], intervention group: 58.1% [n = 162]).…”
Section: Discussioncontrasting
confidence: 53%
“…In contrast to the present study, Pennant et al documented significantly higher vaccination rates for pneumococci (after intervention: chronic lung disease: 79%, rheumatology disease: 87%), but especially for influenza (after intervention: allergy: 64%, infectious disease: 86%). However, the pre‐intervention vaccination rates were already well above the vaccination rates of our present study . In a study conducted by Sansom et al in a sexually transmitted disease clinic for men who have sexual relations with other men, a telephone reminder was ineffective regarding the proportion of patients who completed the basic immunization with the third dose of the hepatitis B vaccination (control group: 59.2% [n = 145], intervention group: 56.3% [n = 157]) or the second dose of the hepatitis A vaccination (control group: 62.9% [n = 154], intervention group: 58.1% [n = 162]).…”
Section: Discussioncontrasting
confidence: 53%
“…Disparities in immunization rates of Medicare beneficiaries between the African Americans and Whites are well documented in prior research (Pennant et al, 2015). Using national data from the Behavioral Risk Factor Surveillance System to perform a multilevel analysis of health care coverage, Anderson and Fullerton (2012) showed that the causal mechanisms of the gaps were attributable to racial residential segregation and poverty.…”
Section: Introductionmentioning
confidence: 78%
“…As noted by the American Lung Association (2014), immunizations for influenza and pneumonia among the elderly are imperative for health promotion. Research studies on multiple barriers to influenza and pneumonia immunization for adults have specified financial barriers (Gorshka-Ciebiada et al, 2015; Hebert et al, 2005; National Vaccine Advisory Committee, 2011), low health literacy (Sudore et al, 2006), ineffective reminder system (Johnson, Nichol, & Lipcznski, 2008; Multuck & Flower, 2008) and poor access to primary care services (Pennant et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Several QI strategies in the literature have been described to improve the rates of pneumococcal vaccinations [ 23 , 24 , 25 ]. One study described a simple physician reminder document as sufficient to produce a significant improvement in pneumococcal vaccination in ambulatory rheumatology clinics.…”
Section: Discussionmentioning
confidence: 99%